1996
DOI: 10.1038/bjc.1996.177
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine phosphorylase/platelet-derived endothelial cell growth factor expression associated with hepatic metastasis in gastric carcinoma

Abstract: Summary It is known that angiogenesis plays an important role in the growth and metastasis of solid tumours. Several angiogenic factors have been identified and platelet-derived endothelial cell growth factor (PD-ECGF) is thought to be one such factor. Recently, it was reported that thymidine phosphorylase (dThdPase) is identical to PD-ECGF. Using immunohistochemical staining with an anti-dThdPase antibody, we investigated the correlation between dThdPase expression and the microvessel density in 120 gastric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
108
3
3

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 12 publications
6
108
3
3
Order By: Relevance
“…In the present study, the cases with lymph node metastasis and/or lymph vessel invasion of the cancer disclosed a high T/N ratio of PyNPase mRNA expression in oesophageal cancer. This finding is consistent with previous reports in which malignancies that had high expression of PyNPase demonstrated a highly aggressive behaviour (Maeda et al, 1996;Takebayashi et al, 1996a,b;Tanigawa et al, 1996).…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, the cases with lymph node metastasis and/or lymph vessel invasion of the cancer disclosed a high T/N ratio of PyNPase mRNA expression in oesophageal cancer. This finding is consistent with previous reports in which malignancies that had high expression of PyNPase demonstrated a highly aggressive behaviour (Maeda et al, 1996;Takebayashi et al, 1996a,b;Tanigawa et al, 1996).…”
Section: Discussionsupporting
confidence: 83%
“…It has been reported that intratumoral macrophages express TP in human malignancies 14,15,[17][18][19] and that activated mast cells express TP in atherosclerotic plaques. 25 Activated mast cells also express VEGF 27 and bFGF.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive TP expression has been observed in intratumoral macrophages of colorectal, gastric, and breast carcinoma. 14,15,[17][18][19] Although the intensity of TP expression in stromal and/or tumor 95%CI: 95% confidence interval; TP: thymidine phosphorylase; VEGF: vascular endothelial growth factor; bFGF: basic fibroblast growth factor. a Patients were divided into two groups using cut-off values, means of microvessel, mast cell, and macrophage counts (high and low value groups) or according to TP, VEGF, and bFGF expression patterns (positive and negative tumor groups).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations